Micro-Takaful Coverage Among Low-Income Communities in Malaysia: Exploring the Challenges and Proposed Solutions - Mahmad Robbi, Ahmad Akram; Abdul Wahab, Muadz; Muhammad Zuki, Mohd Faizuddin; Hassan, Rusni (Journal of Islamic Finance, 2025)
Low-income communities in Malaysia continue to be the most vulnerable to health and income risks due to their lack of insurance or takaful coverage. To address the needs of these groups, micro-takaful plays a vital role in advancing financial inclusion by improving access to health and income protection. However, according to a report issued by BNM, takaful market penetration among low-income earners remains limited. Therefore, this study seeks to examine the key challenges contributing to this issue. This study employs comprehensive literature review examinations encompassing books, journals, case studies and policies. Additionally, it includes the field study based on the interviews conducted with the experts in the field. The study finds that Malaysia’s takaful sector faces significant challenges, including demographic trends, economic barriers, and limited engagement with other institutions. To address these challenges, a strategic initiative has been developed to prioritise the inclusion of low-income communities in Malaysia within takaful coverage, supporting their health and income sustainability.